Multimodal neuronavigation in preoperative planning and intraoperative orientation in brain tumors surgery - Rozumenko, Volodymyr; Rozumenko, Artem; Yavorskyi, Aleksandr; Bobryk, Ivan (Ukrainian Neurosurgical Journal, 2014)
Purpose. Brain tumors surgery optimization using multimodal neuronavigation (MN). Materials and methods. 443 patients with brain tumors, been operated with MN, were included in the study. Surgical treatment tactics was planned taking into account data of comprehensive clinical and neurological examination and results of neurovisualising methods. For preoperative planning and 3D-tracking system we used intraoperative surgical neuronavigation «StealthStation TREON plus» (Medtronic, USA). Results. Tumors subtotal removing was performed in 252 (56.9%) patients, total — in 161 (36.3%), partial — in 30 (6.8%). Clinical estimation of patients’ functional state showed it’s index increasing in postoperative period from 68.4 to 86.2 point (according to Karnofsky scale). Conclusions. Innovative neuroimaging technologies in brain tumors surgery using neuronavigation for preoperative planning and intraoperative control of surgical manipulations allow to provide high accuracy and safety of the surgery, to increase it’s radicalism, to minimize surgical trauma, to reduce the risk of postoperative neurological deficits and to improve life quality of operated patients.